2016
DOI: 10.1155/2016/3942672
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers’ Knowledge and Practice Gap towards Joint Zoonotic Disease Surveillance System: Challenges and Opportunities, Gomma District, Southwest Ethiopia

Abstract: Background. Health care providers play a crucial role for realization of joint zoonotic diseases surveillance by human and animal health sectors, yet there is limited evidence. Hence, this study aimed to determine knowledge and practice gap of health care providers towards the approach for Rabies and Anthrax in Southwest Ethiopia. Methods. A cross-sectional survey was conducted from December 16, 2014, to January 14, 2015. Eligible health care providers were considered for the study. Data were entered in to Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…S1 – S5 ) 57 . Jointly responding to outbreaks may reduce costs and foster collaboration between sectors 56 , as has been seen during investigations of monkeypox 58 , leptospirosis 59 , Rift Valley fever 60 , and anthrax and rabies 61 (Fig. 3 and Supplementary Figs.…”
Section: Methodsmentioning
confidence: 99%
“…S1 – S5 ) 57 . Jointly responding to outbreaks may reduce costs and foster collaboration between sectors 56 , as has been seen during investigations of monkeypox 58 , leptospirosis 59 , Rift Valley fever 60 , and anthrax and rabies 61 (Fig. 3 and Supplementary Figs.…”
Section: Methodsmentioning
confidence: 99%
“…For example, one scenario stated that clinicians in a low-prevalence zone had limited ability to recognize questionable patients, and so on. Medical students lack comprehension of zoonoses, according to research ( 54 ), and there is a link between relative knowledge of different diseases and the frequency or recognition in everyday practice ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that proper and timely diagnosis is one of the major attributes for prevention, control and treatment of human and animal anthrax and controlling epidemics. Studies conducted in Ethiopia have highlighted the importance of early diagnosis and care for controlling disease and preventing the spread of undiagnosed cases 14 15 . Capacity building and training for staffs for the identification of clinical cases is important especially in remote areas.…”
Section: Discussionmentioning
confidence: 99%